Hancornia speciosa latex for biomedical applications: physical and chemical properties, biocompatibility assessment and angiogenic activity - Almeida, Luciane Madureira; Floriano, Juliana Ferreira [UNESP]; Ribeiro, Thuanne Pires; Magno, Lais Nogueira; Lima Silveira da Mota, Ligia Souza [UNESP]; Peixoto, Nei; Mrue, Fatima; Melo-Reis, Paulo; Lino Junior, Ruy de Souza; Oliveira Graeff, Carlos Frederico de [UNESP]; Goncalves, Pablo Jose (Springer, 2014)
The latex obtained from Hancornia speciosa is used in folk medicine for treatment of several diseases, such as acne, warts, diabetes, gastritis and inflammation. In this work, we describe the biocompatibility assessment and angiogenic properties of H. speciosa latex and its potential application in medicine. The physical-chemical characterization was carried out following different methodologies (CHN elemental analyses; thermogravimetric analyses and Fourier transform infrared spectroscopy). The biocompatibility was evaluated through cytotoxicity and genotoxicity tests in fibroblast mouse cells and the angiogenic properties were evaluated using the chick chorioallantoic membrane (CAM) assay model. The physical-chemical results showed that the structure of Hancornia speciosa latex biomembrane is very similar to that of Hevea brasiliensis (commercially available product). Moreover, the cytotoxicity and genotoxicity assays showed that H. speciosa latex is biocompatible with life systems and can be a good biomaterial for medical applications. The CAM test showed the efficient ability of H. speciosa latex in neovascularization of tissues. The histological analysis was in accordance with the results obtained in the CAM assay. Our data indicate that the latex obtained from H. speciosa and eluted in water showed significant angiogenic activity without any cytotoxic or genotoxic effects on life systems. The same did not occur with H. speciosa latex stabilized with ammonia. Addition of ammonia does not have significant effects on the structure of biomembranes, but showed a smaller cell survival and a significant genotoxicity effect. This study contributes to the understanding of the potentialities of H. speciosa latex as a source of new phytomedicines.